The Impact Of Organizational Agility, Customer Service, And Sales Innovation On SME Sales Performance With Digitalization As A Mediator (Study On Smes In Jepara Region) - Zahro, Fathimatuz; Dorojatun Prihandono (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study was to determine the effect of organizational agility, customer services, and Innovative selling on the sales performance of MSMEs in Jepara Regency, through the influence of digitalization. The population used in this study were all MSME owners in Jepara Regency, the number of which was unknown. The sample was 100 respondents using convenience sampling technique. The data collection method used was a questionnaire. This research establishes structural equation modeling (SEM) analysis with SmartPLS 4. The findings are organizational agility and customer services have no effect on sales performance, while sales innovativeness and digitalization have a significant effect on sales performance. Based on the results of specific indirect effects, digitalization is able to mediate the effect of organizational agility and sales innovativeness on sales performance, but digitalization is not able to mediate the effect of customer services on sales performance.